2016
DOI: 10.1186/s41018-016-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Crisis analytics: big data-driven crisis response

Abstract: Disasters have long been a scourge for humanity. With the advances in technology (in terms of computing, communications, and the ability to process, and analyze big data), our ability to respond to disasters is at an inflection point. There is great optimism that big data tools can be leveraged to process large amounts of crisis-related data (in the form of user generated data in addition to traditional humanitarian data) to provide an insight into the fast-changing situation and help drive an effective disast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 36 publications
2
97
0
2
Order By: Relevance
“…Furthermore, the humanitarian principles of humanity, impartiality, neutrality, and independence are still among the core principles that should be observed with any technological solutions. Work on big data and the humanitarian principles has shown that there are potential caveats when it comes to the implementation of Big Data solutions (Qadir et al 2016). Veracity of data and analyses as one of the methodological issues around the use of Big Data in the humanitarian field for example remains just as or even more important when dealing with immutable, distributed ledgers.…”
Section: Concerns and Limitationsmentioning
confidence: 99%
“…Furthermore, the humanitarian principles of humanity, impartiality, neutrality, and independence are still among the core principles that should be observed with any technological solutions. Work on big data and the humanitarian principles has shown that there are potential caveats when it comes to the implementation of Big Data solutions (Qadir et al 2016). Veracity of data and analyses as one of the methodological issues around the use of Big Data in the humanitarian field for example remains just as or even more important when dealing with immutable, distributed ledgers.…”
Section: Concerns and Limitationsmentioning
confidence: 99%
“…1) Satellite imagery: Satellite imagery provides quantitative and qualitative data for disaster management which can help to conduction management operation as well as risk reduction. It can be frequently used for assessing the condition of post-disaster [18]. The major contribution of remote sensing such as high resolution, multi-technical and dimensional imagery that provides support for planning pre and post-disaster assessment.…”
Section: A Big Data Sourcesmentioning
confidence: 99%
“…6) Spatial data: Spatial data is helpful for disaster management especially for vulnerability assessment and prediction of natural hazards. Tomaszewski et al [18] conducted a study on geographic information systems (GIS) and mentioned that GIS data such as FEMA, data feeds, World Bank data, national as well as open street map is helpful for disaster management. Spatial data is frequently used for disaster resilience in the developing countries.…”
Section: ) Simulation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of certain technological solutions to security problems may well rely on oversimplifications of humanitarian challenges, thereby ignoring the complex environments in which humanitarians operate (see Abdelnour and Saeed 2014). Beyond practical questions as the legal and operational consequences of using humanitarian technologies (Meier 2011;Qadir et al 2016), there are more fundamental problems with viewing a technological solution as the application of a neutral "fix" for a variety of problems (Jacobsen 2015).…”
Section: Theorymentioning
confidence: 99%